PENGARUH PENJUALAN RUMPUT LAUT SARGASSUM SP TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI TELUK SASAH KABUPATEN BINTAN TAHUN 2022 - Indah Wulandari; Situmeang Situmeang (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The demand for Sargassum Sp seaweed exports from several countries in Asia, including Vietnam, China, and Japan, continues to arrive. One of them is the very high demand for seaweed from China, reaching 5,000 tons per year, not to mention Japan. PT Panorama Indah in Bima Regency during the COVID-19 pandemic, provided information on 17 shipments made during the previous period, exporting 941.42 tons worth US$252,468.90. Meanwhile, in 2019, it was able to export 2,082.76 tons of Sargassum sp type seaweed worth US$543,757.38. Teluk Sasah is one of the villages in Seri Kuala Lobam District, Bintan Regency, Riau Islands, which supplies Sargassum seaweed for sale. This type of research is quantitative research, research data in the form of numbers and analyzed using statistics. The method used in this study is a survey method and indirect observation. The conclusion of the research on the sale of sargassum seaweed has a significant effect on the economic growth of the people of Teluk Sasah Village, Bintan from the survey results about 64% of the community, especially the Tanjung Talok village, experienced an economic increase. Sales of Sargassum partially significantly influence the economic growth of the community T count = 3.687 2.052, Sales of Sargassum simultaneously have a significant effect on the economic growth of the community. Fcount > F table value = 10.279 > 3.34.